Development of epithelial and mesenchymal regionalization of the human fetal utero‐vaginal anlagen. Issue 4 (13th February 2013) - Fritsch, Helga; Hoermann, Romed; Bitsche, Mario; Pechriggl, Elisabeth; Reich, Olaf
Abstract Literature on the development of the human vagina is abundant; however, contributions concerning the prenatal development of the entire utero‐vaginal anlagen (UVA) are rare or carried out in rodents. The primary epithelial characteristics in the adult vagina and uterus are determined during prenatal development and depend on epithelio‐mesenchymal stroma interaction; thus an investigation summarizing the spatiotemporal distribution of relevant molecular markers in the entire human UVA will be of current interest. We phenotyped epithelial and mesenchymal characteristics in sagittal sections from 24 female fetuses of 14–34 weeks of gestation and two female newborns by immunostaining with cytokeratins 8, 13, 14 and 17, p63, bcl‐2, bmp4, HOX A13, CD31, VEGF, SMA, Pax2 and vimentin. Epithelial differentiation followed a caudal‐to‐cranial direction in the UVA. Due to the cytokeratin profile of cytokeratins 8, 13 and 14, the characteristics of the different epithelial zones in the UVA could already be recognized in middle‐age fetuses. Vaginal epithelium originated from the urogenital sinus in the lower portion and initiated the transformation of vimentin‐positive Müllerian epithelium in the upper vaginal portion. During prenatal development the original squamo‐columnar junction was clearly detectable from week 24 onwards and was always found in the cervical canal. Early blc‐2 positivity within the surrounding mesenchyme of the entire vagina including the portio region pointed to an organ‐specific mesenchymal influence. Prenatal findings in human specimens clearly show that fornix epithelium up to the squamo‐columnar junction is of vaginal Müllerian origin, and the cervical epithelium cranial to the squamo‐columnar junction is of uterine Müllerian origin and includes cells with enough plasticity to transform into squamous epithelium.